S100A8/A9 in Inflammation - Wang, Siwen; Song, Rui; Wang, Ziyi; Jing, Zhaocheng; Wang, Shaoxiong; Ma, Jian (Frontiers in Immunology, 2018)
S100A8 and S100A9 (also known as MRP8 ang MRP14, respectively) are Ca2+ binding proteins belonging to the S100 family. They often exist in the form of heterodimer, while homodimer exists very little because of the stability. S100A8/A9 is constitutively expressed in neutrophils and monocytes as a Ca2+ sensor, participating in cytoskeleton rearrangement and arachidonic acid metabolism. During inflammation, S100A8/A9 is released actively and exerts a critical role in modulating the inflammatory response by stimulating leukocyte recruitment and inducing cytokine secretion. S100A8/A9 serves as a candidate biomarker for diagnosis and follow-up as well as a predictive indicator of therapeutic responses to inflammation-associated diseases. As blockade of S100A8/A9 activity using small-molecule inhibitors or antibodies improves pathological conditions in murine models, the heterodimer has potential as a therapeutic target. In this review, we provide a comprehensive and detailed overview of the distribution and biological functions of S100A8/A9 and highlight its application as a diagnostic and therapeutic target in inflammation-associated diseases.